Seroepidemiological study of SARS-CoV-2 infection in East Java, Indonesia - Megasari, Ni Luh Ayu; Utsumi, Takako; Yamani, Laura Navika; Juniastuti; Gunawan, Emily; Furukawa, Koichi; Nishimura, Mitsuhiro; Lusida, Maria Inge; Mori, Yasuko (PLOS ONE, 2021)
Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to a global pandemic, including Indonesia. However, there are only limited data regarding the precise prevalence of the COVID-19 pandemic in Indonesia. Here, to estimate the magnitude of SARS-CoV-2 infection in East Java, Indonesia, we investigated the prevalence of immunoglobulin G (IgG) antibodies. We enrolled 1,819 individuals from June to December 2020 and observed that the subjects’ overall prevalence of IgG antibody to SARS-CoV-2 was 11.4% (207/1,819). The prevalence of anti-SARS-CoV-2 antibodies differed significantly between the job/occupation groups (P = 0.0001). A greater prevalence of IgG was detected in laboratory technicians (who take samples from suspected cases and deal with polymerase chain reaction [PCR] procedures, 22.2%) compared to medical personnel who see and take direct care of patients with COVID-19 (e.g., physicians and nurses, 6.0%), other staff in medical facilities (2.9%), general population (12.1%) and non-COVID-19 patients (14.6%). The highest prevalence among age groups was in the 40–49-year-olds (14.8%), and the lowest prevalence was in the 20–29-year-olds (7.4%). However, the younger population still showed a higher prevalence than generally reported, suggesting greater exposure to the virus but less susceptibility to the disease. A geographical difference was also observed: a higher prevalence in Surabaya (13.1%) than in Jombang (9.9%). In conclusion, the COVID-19 outbreak among asymptomatic populations was characterized by a high prevalence of infection in East Java, Indonesia.